2012
DOI: 10.1007/s10517-012-1583-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Conscious and Anesthetized Rats under the Action of Angiotensin Converting Enzyme Inhibitors

Abstract: We studied the effects of three various angiotensin converting enzyme inhibitors (enalapril, lisinopril and quinapril) on heart rhythm variability in anesthetized and immobilized rats. In all cases (except for quinapril in experiments on anesthetized animals), the preparations reduced the total rhythm variability and, according to spectrum analysis, increased activity of the parasympathetic autonomic nervous system to different degrees and decreased sympathetic tone. Quinapril and lisinopril produced the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This outcome was represented by the power of the LF band ( Figure 3 , Table 1 ), a reliable parameter of sympathetic activity, since blood vessels receive mainly sympathetic innervation. On the other hand, enalapril treatment reduced global HRV in C57BL/6 mice, corroborating previous reports, which stated that both captopril and enalapril can reduce global HRV ( 22 , 23 ). Interestingly, these studies also observed that HR increases after ACE-inhibitor treatment, as seen in ELA-2 KO mice, which is unexpected since human studies suggest that HR is usually not affected with therapeutic doses of captopril ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…This outcome was represented by the power of the LF band ( Figure 3 , Table 1 ), a reliable parameter of sympathetic activity, since blood vessels receive mainly sympathetic innervation. On the other hand, enalapril treatment reduced global HRV in C57BL/6 mice, corroborating previous reports, which stated that both captopril and enalapril can reduce global HRV ( 22 , 23 ). Interestingly, these studies also observed that HR increases after ACE-inhibitor treatment, as seen in ELA-2 KO mice, which is unexpected since human studies suggest that HR is usually not affected with therapeutic doses of captopril ( 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…[345] In addition, ECG recording of the anesthetized rat lacks validity for HR variability analysis. [67]…”
mentioning
confidence: 99%